1998
DOI: 10.1210/mend.12.6.0123
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Role for RIP140 in Nuclear Receptor Activation

Abstract: Transcriptional regulation of gene expression by nuclear receptors requires negatively and positively acting cofactors. Recent models for receptor activation propose that certain receptors in the absence of ligands can recruit corepressors while ligand binding results in conformational changes leading to the recruitment of coactivators. Previous work has established a coactivator role for the SRC-1 family members as well as an involvement of the coactivators CBP/p300 in nuclear receptor signaling. However, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
133
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(145 citation statements)
references
References 74 publications
9
133
1
2
Order By: Relevance
“…We have provided evidence that BTG1 stimulates TRa1 and RARa transcriptional activity to a similar extent as reported for other coactivators (Monden et al, 1997;Treuter et al, 1998;Ko et al, 2000) and physically interacts with these receptors. As previously shown for PGC1a (Puigserver et al, 1998), we first observed that this interaction occurred in the absence and presence of the respective ligands of each receptor, leading us to study the possibility that, in the absence of ligands, binding of a corepressor molecule to nuclear receptors could impair their ability to interact with BTG1.…”
Section: Btg1 Is a Coactivator Of Positive Regulators Of Myoblast Difsupporting
confidence: 77%
“…We have provided evidence that BTG1 stimulates TRa1 and RARa transcriptional activity to a similar extent as reported for other coactivators (Monden et al, 1997;Treuter et al, 1998;Ko et al, 2000) and physically interacts with these receptors. As previously shown for PGC1a (Puigserver et al, 1998), we first observed that this interaction occurred in the absence and presence of the respective ligands of each receptor, leading us to study the possibility that, in the absence of ligands, binding of a corepressor molecule to nuclear receptors could impair their ability to interact with BTG1.…”
Section: Btg1 Is a Coactivator Of Positive Regulators Of Myoblast Difsupporting
confidence: 77%
“…Northern hybridizations were performed as described previously (24). The RIP140 probe was a radiolabeled BglII/XhoI 1-kb fragment from plasmid pSG5-HAhRIP140 (22).…”
Section: Methodsmentioning
confidence: 99%
“…Expression and Reporter Constructs-The HA-tagged RIP140 expression vector in pSG5, pSG5-HAhRIP140, was kindly provided by Dr. Jan-Ake Gustafsson (Karolinska Institute, Sweden) (22). The reporter gene, containing tandem RAREs fused to the minimal herpes simplex virus-thymidine kinase promoter and luciferase (RARE-TK-Luc), has been described previously (41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, targets the SLC39A6/SNAIL pathway by miR-192 to reduce tumor metastasis in human hepatocellular carcinoma (Lian et al 2016). Nuclear receptor interacting protein 1 (NRIP1) also known as RIP140 transcriptional coregulator is a nuclear protein that specifi cally interacts with the hormone-dependent activation domain AF2 of nuclear hormone receptors and modulates transcriptional activity of the estrogen receptor ESR1 and glucocorticoid receptor NR3C1 (Treuter et al 1998). NRIP1 is a positive regulator of the circadian clock genes expression and involved in the regulation of various oncogenic signaling pathways, participates in the development and progression of solid tumors (Lapierre et al 2015).…”
mentioning
confidence: 99%